Beyond nuclear “pasta” : Phase transitions and neutrino opacity of new “pasta” phases - Alcain, Pablo Nicolás (2014)
In this work, we focus on different length scales within the dynamics of nucleons in conditions according to the neutron star crust, with a semiclassical molecular dynamics model, studying isospin symmetric matter at subsaturation densities. While varying the temperature, we find that a solid-liquid phase transition exists, which can be also characterized with a morphology transition. For higher temperatures, above this phase transition, we study the neutrino opacity, and find that in the liquid phase, the scattering of low momenta neutrinos remain high, even though the morphology of the structures differ significatively from those of the traditional nuclear pasta.